The Future of Learning Institutions in a Digital Age - Davidson, Cathy N.; Goldberg, David Theo (Cambridge The MIT Press, 2009)
In this report, Cathy Davidson and David Theo Goldberg focus on the potential for shared and interactive learning made possible by the Internet. They argue that the single most important characteristic of the Internet is its capacity for world-wide community and the limitless exchange of ideas. The Internet brings about a way of learning that is not new or revolutionary but is now the norm for today's graduating high school and college classes. It is for this reason that Davidson and Goldberg call on us to examine potential new models of digital learning and rethink our virtually enabled and enhanced learning institutions. This report is available in a free digital edition on the MIT Press website at http://mitpress.mit.edu/9780262513593. John D. and Catherine T. MacArthur Foundation Reports on Digital Media and Learning
English
Keywords: Impact of science & technology on society; Educational equipment & technology, computer-aided learning (CAL); Impact of science and technology on society; Educational equipment and technology, computer-aided learning (CAL)